2012
DOI: 10.1177/1934578x1200700924
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Inhibitor from the Malaysian Medicinal Plant Goniothalamus andersonii and Related Species

Abstract: A crude methanol extract of Goniothalamus andersonii J. Sinclair strongly inhibited elongation of lettuce (Lactuca sativa L.) radicles. We conducted bioassayguided purification of G. andersonii bark extract and obtained goniothalamin as the major bioactive compound. Its EC 50 values against elongation of lettuce radicles and hypocotyls were 50 and 125 µmol L −1 , respectively. Among the six species tested, timothy was the most sensitive to goniothalamin. Quantification of this compound in other Goniothalamus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Plant materials: A bark sample of G. andersonii used for the isolation of goniothalamin was collected in Sri Aman, Sarawak, Malaysia, in October 2010. Purification of goniothalamin was conducted according to the method of the preceding study [4]. After methanol extraction of the bark, goniothalamin was partitioned with n-hexane, ethyl acetate, and n-butanol, and the ethyl acetate layer was subjected to an HPLC system equipped with a Waters 626 pump (Milford, MA, USA), a Waters 996 photodiode array detector, and a reversed-phase column (Inertsil ODS-3, 5 μm, 4.6 mm i.d., 250 mm length, GL Sciences Inc., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant materials: A bark sample of G. andersonii used for the isolation of goniothalamin was collected in Sri Aman, Sarawak, Malaysia, in October 2010. Purification of goniothalamin was conducted according to the method of the preceding study [4]. After methanol extraction of the bark, goniothalamin was partitioned with n-hexane, ethyl acetate, and n-butanol, and the ethyl acetate layer was subjected to an HPLC system equipped with a Waters 626 pump (Milford, MA, USA), a Waters 996 photodiode array detector, and a reversed-phase column (Inertsil ODS-3, 5 μm, 4.6 mm i.d., 250 mm length, GL Sciences Inc., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have approached the physiological roles of goniothalamin to some cancer cell lines, and reported that it induces DNA damage and oxidative stress resulting in apoptosis of cancer cells [3a,3b]. During our screening studies of plant allelochemicals, we found that goniothalamin produced by G. andersonii J. Sinclair strongly inhibits plant growth [4]. Although research into the physiological effect of goniothalamin on cancer cells is ongoing in many countries, the effect on plants is poorly understood.…”
mentioning
confidence: 98%
“…A simple and quick bioassay procedure is necessary to evaluate the allelopathic potential of a large number of mushroom samples. Several researchers have developed such methods to evaluate the allelopathic properties for individual plants/compounds [18][19][20][21][22][23][24][25][26]. These methods were designed based on the three main allelochemical release routes of plants: leaf litter leachates, roots exudates (in vitro and roots exudates in the soil), and volatiles.…”
Section: Introductionmentioning
confidence: 99%